Effects of traditional Chinese exercises on mental health in individuals with drug rehabilitee: A systematic review and meta-analysis - Zhang, Yulong; Lu, Shenghua (Frontiers in Public Health, 2022)
Purpose The intent of this systematic review and meta-analysis was to examine the effects of Traditional Chinese Exercise (TCE) on mental health and drug cravings in drug rehabilitees. Methods Six electronic databases (PubMed, Web of Science, MEDLINE, CINAHL, PsycArticles, and CNKI) were searched to identify the potential literature from inception to March 2022. The controlled studies with a pro-posttest design that investigated the effects of TCE on mental health (depression, anxiety, drug craving, and sleep quality) were included. The effect sizes were calculated using the random-effect models with a 95% confidence interval. The Physiotherapy Evidence Database (PEDro) scale was employed to evaluate study quality. Results A total of 10 studies (740 participants, mean age 35 years old) were included in this study. The pooled results showed that TCE produced significant improvements in depression (SMD = 0.65, 95% CI 0.29 to 1.02, p < 0.01), anxiety (SMD = 0.98, 95% CI 0.44 to 1.53, p < 0.01), and drug craving (SMD = 0.87, 95% CI 0.54 to 1.21, p < 0.01) compared to the control group. The subgroup analysis results showed that TCE resulted in significant improvements in depression compared to active intervention (SMD = 0.33, 95% CI 0.07 to 0.60) or passive intervention (SMD = 1.07, 95% CI 0.40 to 1.74). A significant improvement in depression was observed in both male and female drug rehabilitee (p < 0.05). Moreover, Tai Chi (SMD = 0.69, 95% CI 0.19 to 1.18) or Qigong (SMD = 0.49, 95% CI 0.24 to 0.74) exercise, 3–4 times per week (SMD = 1.06, 95% CI 0.39 to 1.74) or ≥5 times (SMD = 0.39, 95% CI 0.12 to 0.66), >45 min (SMD = 0.62, 95% CI 0.09 to 1.15) or ≤ 45 min (SMD = 0.68, 95% CI 0.10 to 1.27), and for a duration of 12 weeks (SMD = 0.84, 95% CI 0.15 to 1.54) produced significant improvement in depression. Conclusion This current study suggests that TCE (Tai Chi, Qigong) may have benefits in alleviating depression, anxiety, and drug cravings in drug rehabilitees. Further studies are required to verify our results through the implementation of well-designed experimental protocols.